BOYO KALI COMAL DANCE AS AN INSPIRATION FOR ILLUSTRATIVE ARTWORKS IN A SUREALISTIC REPRESENTATIVE APPROACH - Rizqiono, Muhammad; Mujiyono (Universitas Negeri Semarang, 2025)
This writing raises the theme of the legendary story of the Boyo Kali Comal dance which is realized in an illustration work with a surrealistic representative approach. The purpose of creating this work is to explain the movements, values, and stories contained in the Boyo Kali Comal Dance through surrealistic illustrations. This work aims to reintroduce the richness of local culture to the community with a visual approach. The creation of this work is divided into three stages, namely pre-production, production, and post-production. The resulting work consists of two works. In the analysis of the work, Roland Barthes' semiotic approach is used to interpret the meaning and messages implied in each visual element. The first work entitled